Spherical (LPSGY) FO high-entropy nano material as well as preparation method and application thereof

The preparation of spherical (LPSGY)FO high-entropy nanomaterials by ultrasonic sequential method solves the problem of lack of gas detection materials in the existing technology and achieves efficient gas detection effect, especially in the application of acetone gas sensors.

CN119263356APending Publication Date: 2025-01-07BOHAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411393003.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

There is a lack of high-entropy materials suitable for gas detection in the current technology, and their application in gas sensors is particularly limited.

Method used

Spherical (LPSGY)FO high-entropy nanomaterials were prepared using an ultrasonic sequential method. This involved dissolving lanthanum nitrate hexahydrate, praseodymium nitrate hexahydrate, samarium nitrate hexahydrate, gadolinium nitrate hydrate, ytterbium nitrate pentahydrate, ferric nitrate hexahydrate, and sodium hydroxide. Sodium hydroxide solution was then added dropwise under ultrasonic conditions. Following centrifugation, washing, drying, and calcination, spherical (La0.2Pr0.2Sm0.2Gd0.3Yb0.1)FeO3 high-entropy nanomaterials were formed.

Benefits of technology

The prepared spherical high-entropy nanomaterials have a larger specific surface area and higher detection efficiency, and can effectively detect gases such as acetone. In particular, they have good selectivity and detection effect for acetone gas, and are suitable for the preparation of acetone gas sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263356A_ABST
    Figure CN119263356A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of gas sensitive materials, in particular to a spherical (LPSGY) FO high-entropy nano material as well as a preparation method and application thereof. The preparation method of the spherical (LPSGY) FO high-entropy nano material comprises the following steps: mixing lanthanum nitrate hexahydrate, praseodymium nitrate hexahydrate, samarium nitrate hexahydrate, gadolinium nitrate hydrate, ytterbium nitrate pentahydrate, ferric nitrate hexahydrate and sodium hydroxide, dissolving in deionized water, and stirring at normal temperature and normal pressure to obtain a mixed solution; placing the mixed solution in an ultrasonic cell wall breaking machine, dropwise adding excessive sodium hydroxide solution under an ultrasonic condition, stirring, cooling to room temperature, centrifuging, washing, drying and grinding to obtain (LPSGY) FO precursor powder; according to the present invention, the LPSGY FO precursor powder is calcined to obtain the spherical LPSGY FO high-entropy nanometer material, the high-entropy material can be used for gas detection, and due to the characteristics of the spherical structure, more detected gas is allowed to pass through, such that the gas contact surface is increased, the large specific surface area is provided, the detection effect is good, and the detection efficiency is high;
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas-sensitive materials, and in particular to a spherical (LPSGY)FO high-entropy nanomaterial and a preparation method and application thereof. Background Art

[0002] Gas sensing is an indispensable core technology in many fields, and it plays a vital role in environmental monitoring and industrial production process management. Compared with those methods that rely on complex and heavy equipment and technology, such as spectrophotometry or mass spectrometry, oxide semiconductor gas sensors have attracted widespread attention due to their simple operation, high sensitivity, good stability, and fast response and recovery characteristics.

[0003] Due to the introduction of multiple elements with different ionic radii, high entropy perovskite (HEPs) oxide materials have larger lattice distortion, more diverse electronic structures and richer active sites than ordinary perovskite oxide materials. In recent years, HEPs have been widely studied in various fields such as catalysis and degradation, but there are currently limited reports on their application in gas sensing.

[0004] The A site of HEPs is usually occupied by rare earth elements, while the B site is occupied by transition metal elements. The tunability of the A and B sites provides opportunities to improve the gas sensing performance of the material.

[0005] How to prepare a new high-entropy material so that it can be used in gas detection has become a technical problem that urgently needs to be solved. Summary of the invention

[0006] The purpose of the present invention is to provide a spherical (LPSGY)FO high entropy nanomaterial and a preparation method and application thereof, so as to solve the technical problem of lack of high entropy materials for gas detection in the prior art.

[0007] In order to achieve the above-mentioned object, according to a first aspect of the present invention, a method for preparing a spherical (LPSGY)FO high entropy nanomaterial is provided, comprising the following steps: dissolving lanthanum nitrate hexahydrate, praseodymium nitrate hexahydrate, samarium nitrate hexahydrate, gadolinium nitrate hydrate, ytterbium nitrate pentahydrate, ferric nitrate hexahydrate and sodium hydroxide in deionized water, and stirring at room temperature and pressure to obtain a mixed solution; placing the mixed solution in an ultrasonic cell wall disruptor, dripping an excess of sodium hydroxide solution under ultrasonic conditions, stirring, cooling to room temperature, and then centrifuging, washing, drying and grinding to obtain a (LPSGY)FO precursor powder; and calcining the (LPSGY)FO precursor powder to obtain a spherical (LPSGY)FO high entropy nanomaterial.

[0008] Further, 0.54% to 1.61% of lanthanum nitrate hexahydrate, 0.54% to 1.61% of praseodymium nitrate hexahydrate, 0.54% to 1.61% of samarium nitrate hexahydrate, 1.08% to 2.15% of gadolinium nitrate hexahydrate, 0.27% to 0.81% of ytterbium nitrate pentahydrate, 4.03% to 6.72% of ferric nitrate hexahydrate and 7.53% to 9.14% of sodium hydroxide in a mass ratio are mixed and dissolved in 82.53% to 85.9% of deionized water, and stirred for 30 minutes at a temperature of 25° C. and a pressure of 101.3 kPa to obtain a mixed solution.

[0009] Furthermore, a sodium hydroxide solution of 9% or more is added dropwise at a rate of 0.1 ml / min to 0.5 ml / min under ultrasonic conditions of 250 W to 450 W, stirred for 8 min to 15 min, and ground into powder after centrifugation, washing, and drying at 50° C. to 80° C. to obtain a (LPSGY)FO precursor powder.

[0010] Furthermore, the (LPSGY)FO precursor powder is calcined at 800°C to 1000°C for 2h to 6h to obtain a spherical (LPSGY)FO high entropy nanomaterial; the spherical (LPSGY)FO high entropy nanomaterial is a spherical structure of 1μm to 3μm formed by aggregation of 10nm to 50nm nanoparticles; wherein, (LPSGY)FO is (La 0.2 Pr 0.2 Sm 0.2 G 0.3 Yb 0.1 )The abbreviation of FeO3.

[0011] According to a second aspect of the present invention, a spherical (LPSGY)FO high entropy nanomaterial is provided. The spherical (LPSGY)FO high entropy nanomaterial is prepared by using the above-mentioned method for preparing the spherical (LPSGY)FO high entropy nanomaterial.

[0012] According to a third aspect of the present invention, there is provided an application of a spherical (LPSGY)FO high entropy nanomaterial as a gas-sensitive semiconductor material, wherein the spherical (LPSGY)FO high entropy nanomaterial is the above-mentioned spherical (LPSGY)FO high entropy nanomaterial.

[0013] Furthermore, the gas-sensitive semiconductor material is used to detect acetone gas, methanol gas, ethylene glycol gas, ethanol gas, ammonia gas, nitrogen dioxide gas or carbon dioxide gas.

[0014] According to a fourth aspect of the present invention, there is provided an application of a spherical (LPSGY)FO high entropy nanomaterial in the preparation of an acetone gas sensor, wherein the spherical (LPSGY)FO high entropy nanomaterial is the above-mentioned spherical (LPSGY)FO high entropy nanomaterial.

[0015] Furthermore, the preparation method of the acetone gas sensor includes the following steps: grinding a spherical (LPSGY)FO high entropy nanomaterial to obtain a spherical (LPSGY)FO high entropy nanomaterial powder; mixing the spherical (LPSGY)FO high entropy nanomaterial powder with deionized water and ethanol to form a viscous paste slurry; uniformly coating the viscous paste slurry on the surface of a metal electrode on an alumina ceramic tube; uniformly applying the viscous paste slurry around the metal electrode; fixing the coated alumina ceramic tube on a base, and installing a heating resistance wire therein to form a gas sensitive element, the resistance wire being connected to the heating end at the center of the base, thereby completing the assembly of the acetone gas sensor; placing the assembled acetone gas sensor on an aging table for aging treatment, thereby completing the preparation of the acetone gas sensor.

[0016] Furthermore, a spherical (LPSGY)FO high entropy nanomaterial with a mass percentage of 33% to 35% is ground in a mortar to obtain a spherical (LPSGY)FO high entropy nanomaterial powder; the spherical (LPSGY)FO high entropy nanomaterial powder is mixed with 55% to 58% by mass of deionized water and 9% to 12% by mass of ethanol to form a viscous paste slurry; the viscous paste is evenly coated on the surface of the metal electrode on the alumina ceramic tube using a screen printing technique, and the coating operation is repeated 5 to 7 times; the viscous paste is evenly applied around the metal electrode using a brush coating method. The paste slurry is applied in 1 to 3 layers; the coated alumina ceramic tube is fixed on a six-legged base, and a heating resistance wire is installed therein to form a gas sensitive element, and the resistance wire is connected to the heating end at the center of the base, and the assembly of the acetone gas sensor is completed; the assembled acetone gas sensor is placed on an aging table, and an aging treatment is performed at 100°C to 200°C for 70 hours to 75 hours to complete the preparation of the acetone gas sensor; wherein the stable resistance value of the acetone gas sensor in acetone atmosphere is Rg, and the stable resistance value in air is Ra, and its response performance is characterized by the ratio of Rg / Ra.

[0017] By applying the technical solution of the present invention, a preparation method of a spherical (LPSGY)FO high entropy nanomaterial is provided. According to the preparation method, a spherical (LPSGY)FO high entropy nanomaterial can be prepared. The high entropy material can be used for gas detection, and due to the characteristics of its spherical structure, more gas to be measured can be allowed to pass through, so that the gas contact surface is increased, the surface area is larger, the detection effect is better, and the detection efficiency is higher. The spherical (LPSGY)FO high entropy nanomaterial can be used as a gas-sensitive semiconductor material. Moreover, it is verified by experiments that the spherical (LPSGY)FO high entropy nanomaterial prepared by the present invention has good selectivity for acetone and good detection effect, and can be applied to the preparation of acetone gas sensors.

[0018] Based on the implementations provided in the above aspects, the present application can also be further combined to provide more implementations. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 The XRD pattern of the (LPSGY)FO high entropy nanomaterial obtained in Example 1;

[0021] Figure 2 This is a SEM image of the (LPSGY)FO high entropy nanomaterial obtained in Example 1; wherein, Figure 2 (a) is the SEM image at 10 μm scale. Figure 2 (b) is the SEM image at a scale of 500 nm. Figure 2 (c) is the SEM image at 200 nm scale;

[0022] Figure 3 The response curve of the (LPSGY)FO high entropy nanomaterial obtained in Example 1 to 100 ppm acetone at different working temperatures;

[0023] Figure 4 This is the dynamic response recovery curve of the (LPSGY)FO high entropy nanomaterial obtained in Example 1 to 100 ppm acetone;

[0024] Figure 5 The response curve of the (LPSGY)FO high entropy nanomaterial obtained in Example 1 to different concentrations of acetone;

[0025] Figure 6 (a) is the SEM image of the (LPSGY)FO high entropy nanomaterial obtained in Comparative Example 1;

[0026] Figure 6 (b) is the SEM image of the (LPSGY)FO high entropy nanomaterial obtained in Comparative Example 3. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0028] The invention provides a preparation method of a spherical (LPSGY)FO high entropy nanomaterial, comprising the following steps: dissolving lanthanum nitrate hexahydrate, praseodymium nitrate hexahydrate, samarium nitrate hexahydrate, gadolinium nitrate hydrate, ytterbium nitrate pentahydrate, ferric nitrate hexahydrate and sodium hydroxide in deionized water, stirring at room temperature and pressure to obtain a mixed solution; placing the mixed solution in an ultrasonic cell wall breaking machine, dripping an excess of sodium hydroxide solution under ultrasonic conditions, stirring, cooling to room temperature, centrifuging, washing, drying and grinding to obtain a (LPSGY)FO precursor powder; calcining the (LPSGY)FO precursor powder to obtain a spherical (LPSGY)FO high entropy nanomaterial. In this way, according to the preparation method, a spherical (LPSGY)FO high entropy nanomaterial can be prepared, and the high entropy material can be used for gas detection, and due to the characteristics of its spherical structure, more measured gases are allowed to pass through, so that the gas contact surface is increased, it has a larger specific surface area, a better detection effect, and a higher detection efficiency.

[0029] Optionally, 0.54% to 1.61% lanthanum nitrate hexahydrate, 0.54% to 1.61% praseodymium nitrate hexahydrate, 0.54% to 1.61% samarium nitrate hexahydrate, 1.08% to 2.15% gadolinium nitrate hexahydrate, 0.27% to 0.81% ytterbium nitrate pentahydrate, 4.03% to 6.72% ferric nitrate hexahydrate and 7.53% to 9.14% sodium hydroxide are mixed and dissolved in 82.53% to 85.9% deionized water, and stirred for 30 minutes at a temperature of 25° C. and a pressure of 101.3k to obtain a mixed solution. The proportion of each material is calculated by a formula to ensure that the molar fraction of each main element is close to equal to form a target phase and maintain the stability of the phase.

[0030] Optionally, a sodium hydroxide solution of 9% or more is added at a rate of 0.1 ml / min to 0.5 ml / min under ultrasonic conditions of 250 W to 450 W, stirred for 8 min to 15 min, and ground into powder after centrifugation, washing, and drying at 50° C. to 80° C. to obtain a (LPSGY)FO precursor powder. It was found during the experiment that when ultrasound was performed at the above specific wattage and added at a specific rate, the desired precursor could be formed.

[0031] Optionally, the (LPSGY)FO precursor powder is calcined at 800°C to 1000°C for 2h to 6h to obtain a spherical (LPSGY)FO high entropy nanomaterial; the spherical (LPSGY)FO high entropy nanomaterial is a spherical structure of 1μm to 3μm formed by aggregation of 10nm to 50nm nanoparticles; wherein (LPSGY)FO is (La 0.2 Pr 0.2 Sm 0.2 G 0.3 Yb 0.1 ) is the abbreviation of FeO3. It is found through experiments that the desired spherical structure can be obtained by calcining at the above specific temperature, which allows more measured gases to pass through, increases the gas contact surface, and has a larger specific surface area.

[0032] The present invention also provides a spherical (LPSGY)FO high entropy nanomaterial, which is prepared by the above-mentioned method for preparing the spherical (LPSGY)FO high entropy nanomaterial. The high entropy material can be used for gas detection, and due to the characteristics of its spherical structure, it allows more measured gas to pass through, so that the gas contact surface is increased, the gas has a larger specific surface area, the detection effect is better, and the detection efficiency is higher.

[0033] The present invention also provides an application of a spherical (LPSGY)FO high entropy nanomaterial as a gas-sensitive semiconductor material, wherein the spherical (LPSGY)FO high entropy nanomaterial is the above-mentioned spherical (LPSGY)FO high entropy nanomaterial. It has been verified by experiments that the spherical (LPSGY)FO high entropy nanomaterial can be used as a gas-sensitive semiconductor material.

[0034] Optionally, the gas-sensitive semiconductor material is used to detect acetone gas, methanol gas, ethylene glycol gas, ethanol gas, ammonia gas, nitrogen dioxide gas or carbon dioxide gas.

[0035] Since there are too many types of gases to list exhaustively, gas-sensitive semiconductor materials can also be used to detect other types of gases based on actual conditions.

[0036] Acetone is a colorless, flammable compound with a distinctive odor that plays a vital role in various industrial processes. However, long-term exposure to high concentrations of acetone can cause damage to the human nasal cavity and eye area. In addition, there is a significant difference in the exhaled acetone levels between healthy people (300ppb-1ppm) and diabetic patients (≥1.8ppm). Given the potential health risks and the importance of environmental protection, it is crucial to develop gas sensors that can detect acetone at parts per billion (ppb) levels to monitor its low range of concentrations.

[0037] The present invention also provides an application of a spherical (LPSGY)FO high entropy nanomaterial in the preparation of an acetone gas sensor, wherein the spherical (LPSGY)FO high entropy nanomaterial is the above-mentioned spherical (LPSGY)FO high entropy nanomaterial. Experimental verification shows that the spherical (LPSGY)FO high entropy nanomaterial prepared by the present invention has good selectivity for acetone and good detection effect, and can be applied to the preparation of an acetone gas sensor.

[0038] Optionally, the preparation method of the acetone gas sensor includes the following steps: grinding spherical (LPSGY)FO high entropy nanomaterials to obtain spherical (LPSGY)FO high entropy nanomaterial powders; mixing the spherical (LPSGY)FO high entropy nanomaterial powders with deionized water and ethanol to form a viscous paste slurry; uniformly coating the viscous paste slurry on the surface of the metal electrode on the alumina ceramic tube; uniformly applying the viscous paste slurry around the metal electrode; fixing the coated alumina ceramic tube on a base, and installing a heating resistance wire therein to form a gas sensitive element, the resistance wire is connected to the heating end at the center of the base, and the acetone gas sensor is assembled; placing the assembled acetone gas sensor on an aging table for aging treatment, and the preparation of the acetone gas sensor is completed. First, grind the material to avoid agglomeration and expose more fresh surfaces, which helps to improve the contact between conductive particles and thus improve the overall conductivity. Apply it evenly to achieve good coverage and ensure consistent performance in each part. Place the resistance wire in the center to ensure uniform heating of the ceramic tube. Aging can improve the stability and reliability of the acetone gas sensor.

[0039] Optionally, a spherical (LPSGY)FO high entropy nanomaterial with a mass percentage of 33% to 35% is ground in a mortar to obtain a spherical (LPSGY)FO high entropy nanomaterial powder; the spherical (LPSGY)FO high entropy nanomaterial powder is mixed with 55% to 58% deionized water and 9% to 12% ethanol to form a viscous paste slurry; the viscous paste is evenly coated on the surface of the metal electrode on the alumina ceramic tube by screen printing technology, and the coating The operation is repeated 5 to 7 times; the viscous paste is evenly applied around the metal electrode by brushing, and a total of 1 to 3 layers are applied; the coated alumina ceramic tube is fixed on a six-legged base, and a heating resistance wire is installed therein to form a gas-sensitive element, and the resistance wire is connected to the heating end at the center of the base to complete the assembly of the acetone gas sensor; the assembled acetone gas sensor is placed on an aging table and aged for 70 to 75 hours at 100°C to 200°C to complete the preparation of the acetone gas sensor. During the experiment, it was found that the acetone gas sensor had the most stable performance, the highest response value to acetone, and the shortest response recovery time when treated in the above temperature range and aging time.

[0040] Optionally, the stable resistance value of the acetone gas sensor in an acetone atmosphere is Rg, and the stable resistance value in air is Ra, and its response performance is characterized by the ratio of Rg / Ra. Through experimental testing, the sensor has the highest response value to acetone, reaching 38.44.

[0041] Embodiment 1:

[0042] (1) Preparation of (LPSGY)FO precursor powder: At room temperature and pressure, 0.6% lanthanum nitrate hexahydrate, 0.6% praseodymium nitrate hexahydrate, 0.6% samarium nitrate hexahydrate, 1.8% gadolinium nitrate hexahydrate, 0.3% ytterbium nitrate pentahydrate, 4.9% ferric nitrate hexahydrate, and 5.32% sodium hydroxide were mixed and dissolved in 85.88% deionized water, and then placed in an ultrasonic cell disruptor. Under 300W ultrasonic conditions, 9% NaOH solution was dripped at a rate of 0.2ml / min. After complete dripping, stirring was continued for 10min. After cooling to room temperature, the mixture was centrifuged, washed, dried at 70°C, and ground into powder to obtain (LPSGY)FO precursor powder.

[0043] (2) Preparation of spherical (LPSGY)FO high entropy nanometer gas-sensitive material: The precursor powder prepared in step (1) was calcined in air at 900°C with a heating rate of 5°C / min for 5 h to obtain a spherical (LPSGY)FO high entropy nanometer gas-sensitive material. The XRD and SEM images after calcination are shown in FIG. Figure 1 , 2 As shown. Figure 1 XRD shows that there are no other diffraction peaks, indicating that the obtained phase is pure. Figure 2 The SEM image shows that a spherical structure can be formed after calcination at 900°C. The spherical structure allows more gas to pass through, increasing the gas contact surface and having a larger specific surface area.

[0044] Preparation and performance test of spherical (LPSGY)FO high entropy nanomaterials in acetone gas sensor:

[0045] Put the spherical (LPSGY)FO calcined at different temperatures with a mass ratio of 35% in step (2) in a mortar, mix 45% deionized water and 20% ethanol, and grind the mixture into a paste. Then, use screen printing technology to evenly coat the paste slurry on the metal electrode on the alumina ceramic tube, and apply it 6 times in total. Subsequently, use a brushing method to evenly apply the slurry around the metal electrode to complete 2 layers of brushing. Insert the heating wire into the center of the ceramic tube and weld it to the heating end of the six-legged base, then place it in the aging table and age it for 72 hours in an environment of 115 degrees Celsius. The generally recognized gas-sensitive mechanism is that when the (LPSGY)FO material is exposed to the air, the oxygen molecules in the air will adsorb on the surface of the (LPSGY)FO and occupy the vacancies on the surface of the material to form surface adsorbed oxygen (O 2- , O - and O 2- ). During this process, a hole accumulation layer gradually forms on the surface of (LPSGY)FO, resulting in a decrease in the resistance of the sensor and an increase in conductivity. As a typical P-type semiconductor, when (LPSGY)FO is placed in an acetone atmosphere, the oxygen previously absorbed by (LPSGY)FO and occupying holes reacts with these reducing gases to produce CO2 gas and a large number of electrons. These electrons are released back into the conduction band of (LPSGY)FO, causing the hole accumulation layer on the surface of (LPSGY)FO to become thinner, thereby increasing the resistance of the sensor and reducing its conductivity.

[0046] It has been verified by experiments that the spherical high entropy nanomaterial obtained in this embodiment has the highest response value to acetone gas at an operating temperature of 175° C., which is 38.44.

[0047] The welded acetone gas sensor was placed in the CGS-8 gas sensitive analysis system, and the resistance of the sensor in acetone gas and air was recorded at different temperatures. The response value was calculated using the formula Rg / Ra to produce Figure 3 The line chart shown is based on Figure 3 It can be determined that the optimal operating temperature of (LPSGY)FO acetone gas sensor is 175℃.

[0048] Place the welded acetone gas sensor into the CGS-8 gas sensitive analysis system at a working temperature of 175°C. First, according to the formula The amount of acetone solution required to be injected at 100 ppm is calculated, and gas is formed after evaporation. Then, the acetone gas and air are switched to each other as a concentration cycle, and the dynamic response recovery curve at 100 ppm is obtained, as shown in FIG. Figure 4 As shown. Figure 4 It can be seen that the prepared (LPSGY)FO acetone gas sensor has a fast response recovery time.

[0049] The amount of acetone solution required at different concentrations is calculated, and gas is formed after evaporation. Then, the acetone gas and air are switched back and forth as a concentration cycle to obtain the response recovery curves at different concentrations, such as Figure 5 As shown. Figure 5 It can be seen that the prepared (LPSGY)FO acetone gas sensor has a fast response recovery time, the prepared (LPSGY)FO sensor has good response and recovery capabilities, and the detection limit is very low, which is 200ppb.

[0050] Comparative Example 1

[0051] The difference between this comparative example and Example 1 is that after stirring at room temperature and pressure, ultrasound is not performed, and sodium hydroxide solution is not added during ultrasound. The scheme of this comparative example is described in detail below:

[0052] 0.6% lanthanum nitrate hexahydrate, 0.6% praseodymium nitrate hexahydrate, 0.6% samarium nitrate hexahydrate, 1.8% gadolinium nitrate hexahydrate, 0.3% ytterbium nitrate pentahydrate, 4.9% ferric nitrate hexahydrate, and 5.32% sodium hydroxide in a mass ratio are mixed and dissolved in 85.88% deionized water, and stirred at room temperature and pressure, cooled to room temperature, centrifuged, washed, dried at 70°C, and then ground into powder to obtain (LPSGY)FO precursor powder; the obtained precursor powder is calcined at 900°C in air with a heating rate of 5°C / min for 5h to obtain a high entropy nanomaterial with a non-spherical morphology, such as Figure 6 (a) shown.

[0053] It has been verified through experiments that the non-spherical high entropy nanomaterial obtained in this comparative example has no response to gas at an operating temperature of 175°C.

[0054] Comparative Example 2

[0055] The difference between this comparative example and Example 1 is that after stirring at room temperature and pressure, no ultrasound is performed and a sodium hydroxide solution is added. The scheme of this comparative example is described in detail below:

[0056] A mixture of 0.6% lanthanum nitrate hexahydrate, 0.6% praseodymium nitrate hexahydrate, 0.6% samarium nitrate hexahydrate, 1.8% gadolinium nitrate hexahydrate, 0.3% ytterbium nitrate pentahydrate, 4.9% ferric nitrate hexahydrate and 5.32% sodium hydroxide in a mass ratio is dissolved in 85.88% deionized water and stirred at room temperature and pressure, a 9% NaOH solution is added dropwise at a rate of 0.1-0.5 ml / min, stirred for ten minutes, cooled to room temperature, centrifuged, washed, dried at 70°C and ground into powder to obtain a (LPSGY)FO precursor powder; the obtained precursor powder is calcined at 900°C in air with a heating rate of 5°C / min for 5 hours to obtain a high entropy nanomaterial with a non-spherical morphology.

[0057] It has been verified through experiments that the non-spherical high entropy nanomaterial obtained in this comparative example has the highest response to acetone gas at an operating temperature of 175°C, which is 3.97.

[0058] Comparative Example 3

[0059] The difference between this comparative example and Example 1 is that after stirring at room temperature and pressure, ultrasound is performed, and a small amount of sodium hydroxide solution is added during ultrasound. The scheme of this comparative example is described in detail below:

[0060] 0.6% lanthanum nitrate hexahydrate, 0.6% praseodymium nitrate hexahydrate, 0.6% samarium nitrate hexahydrate, 1.8% gadolinium nitrate hexahydrate, 0.3% ytterbium nitrate pentahydrate, 4.9% ferric nitrate hexahydrate, and 5.32% sodium hydroxide in a mass ratio are mixed and dissolved in 85.88% deionized water, and stirred at room temperature and pressure, and then placed in an ultrasonic cell wall disruptor, and 7.5% NaOH solution is dripped at a rate of 0.1-0.5 ml / min under 300W ultrasonic conditions. After complete dripping, stirring is continued for 10 minutes, and after cooling to room temperature, centrifugation, washing, and drying at 70°C are performed and then ground into powder to obtain (LPSGY)FO precursor powder; the obtained precursor powder is calcined at 900°C in air, with a heating rate of 5°C / min, and maintained for 5 hours to obtain a high entropy nanomaterial with a non-spherical morphology, such as Figure 6 (b) as shown.

[0061] It has been verified through experiments that the non-spherical high entropy nanomaterial obtained in this comparative example has the highest response to acetone gas at an operating temperature of 175°C, which is 16.31.

[0062] According to the comparison results of Comparative Examples 1, 2, 3 and Example 1, it can be seen that spherical high-entropy nanomaterials cannot be obtained without ultrasound or without adding filtered sodium hydroxide solution.

[0063] It has been verified experimentally that if excessive NaOH is not added, XRD cannot show phases and the products cannot be identified, the prepared samples are impure, and no spheres are produced.

[0064] Example 2

[0065] This embodiment is for detecting methanol gas.

[0066] The preliminary preparation method of this embodiment is consistent with that of embodiment 1, but the detection gas is different, that is, methanol gas is detected. The sensor's response to methanol is 6.19 at 175°C.

[0067] Example 3

[0068] This embodiment is for detecting ethylene glycol gas.

[0069] The preliminary preparation method of this embodiment is consistent with that of embodiment 1, but the detected gas is different, ethylene glycol gas is detected, and the sensor's response to ethylene glycol is 4.28 at 175°C.

[0070] Example 4

[0071] This embodiment is an embodiment for detecting ethanol gas.

[0072] The preliminary preparation method of this embodiment is consistent with that of embodiment 1, but the detection gas is different, ethanol gas is detected, and the sensor's response to ethanol is 3.61 at 175°C.

[0073] Example 5

[0074] This embodiment is an embodiment for detecting ammonia gas.

[0075] The preliminary preparation method of this embodiment is consistent with that of embodiment 1, but the detection gas is different, ammonia gas is detected, and the sensor's response to ammonia gas is 1.59 at 175°C.

[0076] Example 6

[0077] This embodiment is an embodiment for detecting nitrogen dioxide gas.

[0078] The preliminary preparation method of this embodiment is consistent with that of embodiment 1, but the detected gas is different, that is, nitrogen dioxide gas is detected. The sensor's response to nitrogen dioxide is 2.12 at 175°C.

[0079] Example 7

[0080] This embodiment is an embodiment for detecting carbon dioxide gas.

[0081] The preliminary preparation method of this embodiment is consistent with that of embodiment 1, but the detected gas is different, that is, carbon dioxide gas is detected. The sensor's response to carbon dioxide is 4.33 at 175°C.

[0082] It can be seen from the above-mentioned Examples 1 to 7 that the spherical (LPSGY)FO high-entropy nanomaterial provided in the present application can be used as a gas-sensitive semiconductor material. When the gas-sensitive semiconductor material comes into contact with a specific gas, its resistance value will change significantly, and the performance is determined by the relationship between the change in resistance in the air and the resistance in the specific gas.

[0083] According to the comparison of the above-mentioned Examples 1 to 7, it can be seen that the spherical (LPSGY)FO high entropy nanomaterial provided by the present application has the best selectivity and effect on acetone. Therefore, the spherical (LPSGY)FO high entropy nanomaterial provided by the present application can be used in the preparation of an acetone gas sensor. The acetone gas sensor can be used to detect the presence of acetone at low concentrations.

[0084] It has been verified experimentally that if the ultrasonic condition is not used or excessive NaOH is not added, the XRD cannot show phases and the product cannot be determined. The prepared sample is impure and does not produce a spherical shape. In order to obtain the spherical (LPSGY)FO high entropy nanomaterial to be protected by this application, the present invention uses an ultrasonic sequential method to prepare a spherical (La 0.2 Pr 0.2 Sm 0.2 G 0.3 Yb 0.1 )FeO3 high entropy nanomaterials, and request protection for the application of the material in acetone detection. The invention method uses lanthanum nitrate hexahydrate, praseodymium nitrate hexahydrate, samarium nitrate hexahydrate, gadolinium nitrate hexahydrate, ytterbium nitrate pentahydrate, iron nitrate hexahydrate and sodium hydroxide as raw materials, and synthesizes (La 2+) with spherical morphology under different ultrasonic conditions for the first time by ultrasonic sequential method. 0.2 Pr 0.2 Sm 0.2 G 0.3 Yb 0.1 )FeO3 high entropy nanomaterials. The construction of this high entropy perovskite structure not only significantly improves the sensing performance, but also greatly expands its potential application areas. By precisely controlling the composition, we have successfully created more active sites to optimize the performance of the material under various operating environments, providing valuable theoretical basis and practical guidance for the development of high-performance gas sensors. In addition, (La 0.2 Pr 0.2 Sm 0.2 G 0.3 Yb 0.1 )FeO3, as an acetone gas-sensitive sensing material, has fast reaction and recovery time. Its synthesis process is simple, environmentally friendly, low-cost, and suitable for large-scale production.

[0085] The ultrasonic sequential method means that a specific ultrasonic frequency is dripped into the entire solution system at a specific solution dripping rate to obtain a product.

[0086] The present invention belongs to the field of gas-sensitive materials, and specifically relates to a preparation method of a spherical high-entropy nanomaterial and its gas sensing application. The purpose of the present invention is to provide a spherical high-entropy nanomaterial prepared by an ultrasonic sequential method, which has a simple synthesis process and a small synthesized particle size, and the material is used as a gas-sensitive material for detecting acetone gas.

[0087] In an optional embodiment of the present invention, there is provided a method for synthesizing a spherical (La 0.2 Pr 0.2 Sm 0.2 G 0.3 Yb 0.1 The preparation method of )FeO3((LPSGY)FO) nano high entropy material comprises the following steps: dissolving 0.54% to 1.61% lanthanum nitrate hexahydrate, 0.54% to 1.61% praseodymium nitrate hexahydrate, 0.54% to 1.61% samarium nitrate hexahydrate, 1.08% to 2.15% gadolinium nitrate hexahydrate, 0.27% to 0.81% ytterbium nitrate pentahydrate, 4.03% to 6.72% ferric nitrate hexahydrate, and 7.53% to 9.14% sodium hydroxide in 82.53% to 85.9% deionized water, and then placing the mixture in an ultrasonic cell wall disruptor, and pulsating the mixture at 0.1-0.5 ml / min under 300W ultrasonic conditions. The NaOH solution is dripped at a rate of 100 μg / min, and the stirring is continued for 10 min after the complete dripping. After cooling to room temperature, the mixture is centrifuged, washed, dried at 50°C-80°C, and ground into powder to obtain (LPSGY)FO precursor powder. The (LPSGY)FO precursor powder is calcined at 800-1000°C for 2-6h to obtain spherical (LPSGY)FO high entropy nanomaterials; spherical (LPSGY)FO high entropy nanomaterials are nanoparticles aggregated into a spherical shape, and are 1-3 μm spherical structures composed of 10nm-50nm nanoparticles.

[0088] The preparation method of the acetone gas sensor is as follows: grind the (LPSGY)FO high entropy nanomaterial, mix it with deionized water and ethanol to form a paste, evenly apply it on an alumina ceramic tube, weld it on a six-legged base, and add a heating resistance wire to make a gas sensor, and then age it at 100-200℃ for 72h to obtain a gas sensor. The stable resistance value of the acetone gas sensor in acetone gas is Rg, the stable resistance value in air is Ra, and the response value is expressed as Rg / Ra.

[0089] The (LPSGY)FO high entropy nanomaterial in the present invention is spherical, and the (LPSGY)FO high entropy material was prepared for the first time by ultrasonic sequencing, thereby obtaining a high-performance gas sensor. The results show that the (LPSGY)FO sensor exhibits good response and selectivity to acetone, as well as strong long-term stability, excellent humidity resistance and reproducibility during the test process. These properties are attributed to the different composition adjustments of the high entropy material, combined with its surface properties, which promotes an almost continuous distribution of adsorption sites. This unique interaction not only improves the sensing performance, but also significantly broadens its potential application range. By precisely controlling the composition, more active sites can be created to optimize the performance of the material in various operating environments. This work provides valuable insights into the development of high technology.

[0090] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a spherical (LPSGY)FO high entropy nanomaterial, characterized in that: The steps include: Mix and dissolve lanthanum nitrate hexahydrate, praseodymium nitrate hexahydrate, samarium nitrate hexahydrate, gadolinium nitrate hydrate, ytterbium nitrate pentahydrate, ferric nitrate hexahydrate and sodium hydroxide in deionized water, and stir at room temperature and pressure to obtain a mixed solution; The mixed solution is placed in an ultrasonic cell wall disruptor, and an excess amount of sodium hydroxide solution is added dropwise under ultrasonic conditions, stirred, cooled to room temperature, and then centrifuged, washed, dried, and ground to obtain a (LPSGY)FO precursor powder; The (LPSGY)FO precursor powder is calcined to obtain a spherical (LPSGY)FO high entropy nanomaterial.

2. The preparation method according to claim 1, characterized in that: 0.54% to 1.61% lanthanum nitrate hexahydrate, 0.54% to 1.61% praseodymium nitrate hexahydrate, 0.54% to 1.61% samarium nitrate hexahydrate, 1.08% to 2.15% gadolinium nitrate hexahydrate, 0.27% to 0.81% ytterbium nitrate pentahydrate, 4.03% to 6.72% ferric nitrate hexahydrate and 7.53% to 9.14% sodium hydroxide in a mass ratio are mixed and dissolved in 82.53% to 85.9% deionized water, and stirred for 30 minutes at a temperature of 25° C. and a pressure of 101.3 kPa to obtain the mixed solution.

3. The preparation method according to claim 1, characterized in that: Under ultrasonic conditions of 250W to 450W, a 9% or higher sodium hydroxide solution is added dropwise at a rate of 0.1ml / min to 0.5ml / min, stirred for 8min to 15min, and ground into powder after centrifugation, washing, and drying at 50°C to 80°C to obtain the (LPSGY)FO precursor powder.

4. The preparation method according to claim 1, characterized in that: calcining the (LPSGY)FO precursor powder at 800°C to 1000°C for 2h to 6h to obtain a spherical (LPSGY)FO high entropy nanomaterial; The spherical (LPSGY)FO high entropy nanomaterial is a spherical structure of 1 μm to 3 μm formed by aggregation of nanoparticles of 10 nm to 50 nm; Among them, (LPSGY)FO is (La 0.2 Pr 0.2 Sm 0.2 G 0.3 Yb 0.1 )The abbreviation of FeO3.

5. A spherical (LPSGY)FO high entropy nanomaterial, characterized in that: The spherical (LPSGY)FO high entropy nanomaterial is prepared by the preparation method of the spherical (LPSGY)FO high entropy nanomaterial according to any one of claims 1 to 4.

6. Application of a spherical (LPSGY)FO high entropy nanomaterial as a gas-sensitive semiconductor material, characterized in that: The spherical (LPSGY)FO high entropy nanomaterial is the spherical (LPSGY)FO high entropy nanomaterial according to claim 5.

7. The use according to claim 6, characterized in that: The gas-sensitive semiconductor material is used for detecting acetone gas, methanol gas, ethylene glycol gas, ethanol gas, ammonia gas, nitrogen dioxide gas or carbon dioxide gas.

8. Application of a spherical (LPSGY)FO high entropy nanomaterial in the preparation of an acetone gas sensor, characterized in that: The spherical (LPSGY)FO high entropy nanomaterial is the spherical (LPSGY)FO high entropy nanomaterial according to claim 5.

9. The use according to claim 8, characterized in that: The preparation method of the acetone gas sensor comprises the following steps: Grinding the spherical (LPSGY)FO high entropy nanomaterial to obtain spherical (LPSGY)FO high entropy nanomaterial powder; Spherical (LPSGY)FO high entropy nanomaterial powder was mixed with deionized water and ethanol to form a viscous paste slurry; The viscous paste slurry is uniformly applied on the surface of the metal electrode on the alumina ceramic tube; the viscous paste slurry is uniformly applied around the metal electrode; The coated alumina ceramic tube is fixed on the base, and a heating resistance wire is installed therein to form a gas sensing element. The resistance wire is connected to the heating end at the center of the base, thereby completing the assembly of the acetone gas sensor. The assembled acetone gas sensor is placed on an aging table for aging treatment to complete the preparation of the acetone gas sensor.

10. The use according to claim 9, characterized in that: Using 33% to 35% by mass of spherical (LPSGY)FO high entropy nanomaterials, grinding them in a mortar to obtain spherical (LPSGY)FO high entropy nanomaterial powders; The spherical (LPSGY)FO high entropy nanomaterial powder is mixed with 55% to 58% by mass of deionized water and 9% to 12% by mass of ethanol to form a viscous paste slurry; The viscous paste is evenly coated on the surface of the metal electrode on the alumina ceramic tube by screen printing technology, and the coating operation is repeated 5 to 7 times; Use a brushing method to evenly apply the viscous paste around the metal electrode, applying 1 to 3 layers in total; The coated alumina ceramic tube is fixed on a six-legged base, and a heating resistance wire is installed therein to form a gas sensing element. The resistance wire is connected to the heating end at the center of the base, thereby completing the assembly of the acetone gas sensor. The assembled acetone gas sensor is placed on an aging table and subjected to an aging treatment at 100°C to 200°C for 70 to 75 hours to complete the preparation of the acetone gas sensor. Among them, the stable resistance value of the acetone gas sensor in acetone atmosphere is Rg, and the stable resistance value in air is Ra, and its response performance is characterized by the ratio of Rg / Ra.